Metasurface‐Enabled High‐Resolution Liquid‐Crystal Alignment for Display and Modulator Applications. Issue 1 (15th November 2021) - Wang, Jiawei; Li, Ke; He, Huilin; Cai, Wengfeng; Liu, Jianxun; Yin, Zhen; Mu, Quanquan; Hisao, Vincent K. S.; Gérard, Davy; Luo, Dan; Li, Guixin; Liu, Yan Jun
Abstract: Optical metasurfaces are 2D flat elements that consist of spatially arranged meta‐atoms. By carefully designing the metasurface, it is possible to fully control the properties of light in amplitude, phase, and/or polarization. When merged with liquid crystals (LCs), a metasurface can act as a reconfigurable optical component enabling dynamical control of light. However, many reports ignore the influence of the meta‐atom's geometry on the orientation of LCs. Here, it is proposed to synergistically merge LCs and specially designed gold metasurfaces for multiple optical functions. Gold metasurfaces are designed as a template to align the LC molecules in a resolution of ≤2 µm. Meanwhile, the aligned LCs are used to actively control the polarization of the incident light, further achieving active modulation of the plasmonic resonances of gold metasurfaces. The synergistic mergence of LCs and metasurfaces can enable a designed optical device to work simultaneously in both visible and near infrared ranges, which is highly promising for multiple applications simultaneously, such as high‐resolution display, modulation, anti‐counterfeiting, beam deflection, LiDAR, etc. Abstract : Liquid crystals (LCs) and metasurfaces are synergistically merged for optical multifunctions. The specially designed metasurfaces can provide high‐quality alignment of LCs. Meanwhile, the aligned LCs are also used to actively control the plasmonic resonances of metasurfaces. The synergy of LCs and metasurfaces can enable a designed optical device to work simultaneously in both visible and near infrared ranges.